A dose–response relationship of renin–angiotensin system blockers and beta-blockers in patients with acute heart failure syndrome: a nationwide prospective cohort study. Issue 6 (28th January 2022) - Kim, Kyung An; Kim, Eui-Soon; Youn, Jong-Chan; Lee, Hye Sun; Jeon, Soyoung; Lee, Hae-Young; Cho, Hyun-Jai; Choi, Jin-Oh; Jeon, Eun-Seok; Lee, Sang Eun; Kim, Min-Seok; Kim, Jae-Joong; et al.
Abstract: Aims: It remains unclear if patients with acute heart failure syndrome (AHFS) need to reach the maximally tolerated doses of renin–angiotensin system blockers (RASBs) or beta-blockers (BBs) to obtain a survival benefit. This study evaluated the dose–response relationship between RASBs or BBs and survival in AHFS patients. Methods and results: In total, 5331 patients in the Korean Acute Heart Failure registry were analysed based on the doses of RASBs and BBs at discharge. In AHFS patients, RASB use at discharge was associated with a significant reduction in all-cause mortality risk. This effect was dose-dependent for heart failure with reduced ejection fraction (HFrEF) but did not attain statistical significance for heart failure with preserved ejection fraction (HFpEF). BB use at discharge was associated with reduced all-cause mortality in HFrEF patients but not in HFpEF patients. In an additional analysis of 4613 patients with dosage information at the first post-discharge follow-up visit, a significantly higher mortality risk was associated with the maintenance or withdrawal of RASBs compared with up-titrating the dose in HFrEF patients. Conclusion: Using RASBs or BBs at discharge was associated with improved survival. A dose–response relationship between RASBs and all-cause mortality was evident in AHFS patients with a reduced ejection fraction but not BBs. It is important to initiate and up-titrate RASBs to the maximally tolerated dose in AHFS patients during the transition period, especially for patients with a reduced ejection fraction.